2013
DOI: 10.1002/bdrc.21027
|View full text |Cite
|
Sign up to set email alerts
|

Zebrafish model systems for developmental neurobehavioral toxicology

Abstract: Zebrafish offer many advantages that complement classic mammalian models for the study of normal development as well as for the teratogenic effects of exposure to hazardous compounds. The clear chorion and embryo of the zebrafish allow for continuous visualization of the anatomical changes associated with development, which, along with short maturation times and the capability of complex behavior, makes this model particularly useful for measuring changes to the developing nervous system. Moreover, the rich ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
118
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 163 publications
(120 citation statements)
references
References 83 publications
2
118
0
Order By: Relevance
“…The rate of cell proliferation in the ZFE CNS was not decreased at the concentrations of HgCl 2 assessed in this study (80 to 500 µg/L), while we previously reported that cell proliferation in the ZFE central nervous system was reduced with exposure to methyl mercury concentrations as low as 10 µg/L. These data confirm the potent toxicity of methyl mercury and that HgCl 2 , while slightly less toxic, also is a potent toxicant [79][80]. These data suggest that decreases in cell proliferation may not be the primary mechanism of toxicity for mercuric chloride.…”
Section: Methylsupporting
confidence: 84%
“…The rate of cell proliferation in the ZFE CNS was not decreased at the concentrations of HgCl 2 assessed in this study (80 to 500 µg/L), while we previously reported that cell proliferation in the ZFE central nervous system was reduced with exposure to methyl mercury concentrations as low as 10 µg/L. These data confirm the potent toxicity of methyl mercury and that HgCl 2 , while slightly less toxic, also is a potent toxicant [79][80]. These data suggest that decreases in cell proliferation may not be the primary mechanism of toxicity for mercuric chloride.…”
Section: Methylsupporting
confidence: 84%
“…Zebraish has been used extensively to elucidate basic mechanisms underlying behavioural toxicology [86]. Zebraish was also employed as a model for identifying sex-speciic efects on social interactions induced by developmental BPA exposure [87,88].…”
Section: Efects On Nervous System and Behaviourmentioning
confidence: 99%
“…Zebraish embryos exposed to BPA also showed signs of feminized brains [86]. Kinch et al [93] investigated morphological changes to developing zebraish caused by exposure to BPA including changes in body length, pericardia (heart) and the head.…”
Section: Other Miscellaneous Efectsmentioning
confidence: 99%
“…The ZF embryos are small (1 to 5 mm), depending on the stage of development) and are translucent. This fact makes them suitable for handling and use (Lele and Krone, 1996;Bailey et al, 2013). Most of the citations of ZF as experimental model refers to the use of embryos and larvae.…”
Section: Of the Zebrafish As Experimental Modelmentioning
confidence: 99%